Foundations of Behavioral Health 2019
DOI: 10.1007/978-3-030-18435-3_10
|View full text |Cite
|
Sign up to set email alerts
|

The Behavioral Health of American Indian/Alaska Native Populations: Risk and Resiliency

Abstract: Risk andProtective Factors Project found the prevalence of DSM-IV disorders was 35.7% for women to nearly 50% for men (Beals et al., 2005). The most common disorder for women was post-traumatic stress disorder and for men, alcohol abuse and dependence. Significant levels of comorbidity were found among those with depressive and/or anxiety and substance use disorders (Beals et al., 2005).To fully understand the behavioral health disparities experienced by AI/AN, it is critical to examine the context in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 117 publications
(149 reference statements)
2
13
0
Order By: Relevance
“…Our results are consistent with recent research indicating higher levels of pre-existing health risks and financial insecurity among racial/ethnic minority groups are associated with increased internalizing disorders during the pandemic (Baldwin et al, 2020;Chen, 2019;Longmire-Avital, 2018;McKnight-Eily et al, 2021), and also demonstrates that prescription insecurity is contributing to mental health risk beginning at the first large scale wave of the virus in 2020. Prior studies have found employment to be a protective factor against mental health problems (McGee & Thompson, 2015;Paul & Moser, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our results are consistent with recent research indicating higher levels of pre-existing health risks and financial insecurity among racial/ethnic minority groups are associated with increased internalizing disorders during the pandemic (Baldwin et al, 2020;Chen, 2019;Longmire-Avital, 2018;McKnight-Eily et al, 2021), and also demonstrates that prescription insecurity is contributing to mental health risk beginning at the first large scale wave of the virus in 2020. Prior studies have found employment to be a protective factor against mental health problems (McGee & Thompson, 2015;Paul & Moser, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…During the COVID-19 pandemic, depression and anxiety among AIAN, Asian, Black, and Latinx people have also increased (Baldwin et al, 2020;Chen, 2019;McKnight-Eily et al, 2021). Although prepandemic prevalence rates of major depression and generalized anxiety among these groups were often reported to be similar to or lower than non-Hispanic Whites, these findings have been attributed to the fact that people of color in the U.S. seek mental health clinical care at rates well below their need, face discrimination during diagnosis and treatment, suffer from misdiagnosis and clinician bias, and within their communities mental health may be shrouded by silence and shame (Baldwin et al, 2020;Harkness et al, 2020;Mental Heath America, 2021;Novacek et al, 2020;Vilsaint et al, 2019). Further, although prior research has repeatedly reported on the protective effect of employment on mental health (McGee & Thompson, 2015;Paul & Moser, 2009), during the pandemic, employed individuals, especially those whose work involves in-person contact, are experiencing higher levels of depression and anxiety (McKnight-Eily et al, 2021;Mehdi et al, 2020).…”
Section: Social Determinants Of Mental Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…These disparities are rooted in long-standing racial inequities in medical and behavioral health treatment utilization, access to culturally relevant health services, treatment satisfaction and trust, and service outcomes (Ben et al, 2017; Chen et al, 2019; Manuel, 2018; Melillo, 2020). During the COVID-19 pandemic, depression and anxiety among AIAN, Asian, Black, and Latinx people have also increased (Baldwin et al, 2020; Chen et al, 2019; McKnight-Eily et al, 2021). Prepandemic prevalence rates of major depression and generalized anxiety among these groups have often been reported to be similar to or lower than non-Hispanic Whites.…”
Section: Racial Discrimination and Mental Healthmentioning
confidence: 99%
“…The Coronavirus Victimization Distress Scale (CVDS) is a fiveitem scale adapted from the Daily Heterosexist Experiences Questionnaire (Balsam et al, 2013), lesbian, gay, bisexual, transsexual (LGBT) People of Color Microaggressions Scale (Balsam et al, 2011), and Adolescent Discrimination Distress Index (Fisher et al, 2000). The items assess distress in response to different instances of victimization, for example, "because someone thought I was infected with the Coronavirus" (see Table 3).…”
Section: Coronavirus Victimization Distress Scalementioning
confidence: 99%